Non-linear dynamics simulation-based testing to create operating envelopes for autonomos UAS inspection missions - Page, V.; Dadswell, C.; Jump, M. (My University, 2021)
This paper uses stitched linear and non-linear models to simulate the dynamics of an autonomous TRex-700E model helicopter in order to determine its operating envelope. The helicopter is simulated carrying out an oil rig inspection mission and the wind speed and direction are used to define its operating limits. These limits were determined by applying a series of cost functions, which use operator set performance requirements, to the velocities, attitudes, controls inputs, and position of the UAS over the course of the mission. It was found that for benign wind conditions, in this case <10 knots wind speed, the linear models provide a reasonable approximation. However, as the operating limits reached, the non-linear and linear models diverge. Therefore, to determine the operating limits in harsher wind conditions, the non-linear models would be required.